PERAN MAHASISWA DALAM MENINGKATKAN KESADARAN BERIBADAH DI DUSUN V DESA KUNGKAI BARU - Agustio, Winaldi; Kurniawan, Angga; Desvaria, Fitri; Fadhilah, Arum; Alya Adilla, Maulani (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
This study aims to identify the role of students in enhancing religious awareness within the community of Dusun V, Desa Kungkai Baru, Air Periukan, Seluma. The research was conducted from June 24, 2024, to August 3, 2024, using an observational method. Students actively participated in implementing programs aimed at increasing religious awareness among the local community. The results show a significant improvement in religious awareness following the implementation of these programs. In conclusion, the students' role has proven effective in facilitating positive changes in the worship patterns of the Dusun V, Desa Kungkai Baru community.